Respon Pertumbuhan dan Produksi Semangka (Citrullus vulgaris S.) dengan Pemberian Pupuk Organik Cair (POC) - Diah Eka Puspita; Basri Basri (Serambi Saintia : Jurnal Sains dan Aplikasi, 2017)
Plant Response and Crop Watermelon Production (Citrullus Vulgaris Schard.) With the provision of Liquid Organic Fertilizer. The purpose of this study to determine the growth and production of watermelon plants treated with liquid organic fertilizer. The study was conducted in Bambel District, Southeast Aceh, with an altitude of 220 meters above sea level. The research using non factorial Randomized Block Design (RAK) consist of 4 levels: M0 = Control, M1 = 75 cc / l liter air / polybag, M2 = 150 cc / l liter air / polybag and M3 = 200 cc / l liter air / polybag with 4 replications. The parameters observed were plant stem length (cm), flowering time (day), fruit weight of first harvest (gr). From this research, it can be concluded that Organic Fertilizer Response (M) shows an unstable difference in observation parameters of the third flowering time and the interaction on observation parameters of plant stem length at plant age 25 DAP, 50 DAP and 75 DAP, harvest time of first stage and the first fruit weight per sample of each plot shows significant effects. On observation of flowering time, the provision of liquid organic fertilizer gives no significant effect on each flowering time, observed that flowering I,II,and III. For the parameters of the first harvest, watermelon had a significant effect with the heaviest weight on the M1 treatment Keywords : Watermelon, Liquid Organik Fertilizer, Growth, Production